Exploring the biological basis for the identification of different syndromes in ischemic heart failure based on joint multi-omics analysis - Zhang, Yilin; Wei, Jingjing; Qiao, Lijie; Yu, Rui; Ren, Hongjie; Zhao, Anshe; Sun, Yang; Wang, Aolong; Li, Bin; Wang, Xinlu; Zhu, Mingjun (Frontiers in Pharmacology, 2025)
BackgroundIHF is a major chronic disease that seriously threatens human health. Qi deficiency and blood stasis syndrome (QDBS), Yang deficiency with blood stasis syndrome (YDBS) and Yang deficiency and blood stasis with fluid retention syndrome (YDBSFR) are the basic syndromes of IHF in Chinese medicine. This study aims to explore the biological basis of the three IHF syndromes through integrated multi-omics research.MethodsWe analyzed and integrated transcriptomic, proteomic, and targeted metabolomic data from IHF patients and healthy persons to obtain the key biomarkers and enriched pathways of QDBS, YDBS and YDBSFR(Registration No.: ChiCTR2200058314). These biomarkers were combined with clinical indicators to construct the “Disease-Syndromes-Clinical phenotypes-Biomarkers-Pathways” network, and the obtained differential genes and proteins were externally validated.ResultsThe potential biomarkers for QDBS included SDHD, IL10, ACTG1, VWF, MDH2, COX5A, Valeric acid, Succinic Acid and L-Histidine, which were predominantly enriched in TCA cycle, oxidative phosphorylation, platelet activation, and neutrophil extracellular trap formation pathways, demonstrating associations with energy metabolism, coagulation system, and immune-inflammatory responses.YDBS potential biomarkers included TSHR, PRKG1, ATP1A2, GNAI2, APOA2, PLTP, 3-Hydroxybutyrate, Hexadecanoic acid and Palmitelaidic acid, and the combined pathways were mainly enriched in thyroid hormone synthesis, regulation of lipolysis in adipocytes, cholesterol metabolism and PPAR signaling pathways, correlating with hormonal regulation and lipid metabolism. The potential biomarkers of YDBSFR were CNGB1, KCNMA1, PIK3R2, HSPA8, C3, FH, Oxamic acid, N-Acetyl-L-alanine, 4-Hydroxyhippuric acid, and the combined pathways were mainly enriched in aldosterone-regulated sodium reabsorption, cGMP-PKG signaling pathway, neutrophil extracellular trap formation and TCA cycle signaling pathways, which are related to hormone regulation, signal transduction, immune-inflammatory response and energy metabolism. Platelet activation was involved in the whole process of IHF. External validation demonstrated the above core targets.ConclusionThis study investigated the biological basis of QDBS, YDBS and YDBSFR in IHF from a modern biomedical perspective, providing references for the objective research of TCM syndrome differentiation.